Two-Dimensional sixteen channel transmit/receive coil array for cardiac MRI at 7.0 T: Design, evaluation, and application - Thalhammer, Christof; Renz, Wolfgang; Winter, Lukas; Hezel, Fabian; Rieger, Jan; Pfeiffer, Harald; Graessl, Andreas; Seifert, Frank; Hoffmann, Werner; von Knobelsdorff-Brenkenhoff, Florian; Tkachenko, Valeriy; Schulz-Menger, Jeanette; et al. (Journal of magnetic resonance imaging, 2012)
Purpose: To design, evaluate, and apply a 2D 16‐channel transmit/receive (TX/RX) coil array tailored for cardiac magnetic resonance imaging (MRI) at 7.0 T. Materials and Methods: The cardiac coil array consists of two sections each using eight elements arranged in a 2 × 4 array. Radiofrequency (RF) safety was validated by specific absorption rate (SAR) simulations. Cardiac imaging was performed using 2D CINE FLASH imaging, T 2* mapping, and fat–water separation imaging. The characteristics of the coil array were analyzed including parallel imaging performance, left ventricular chamber quantification, and overall image quality. Results: RF characteristics were found to be appropriate for all subjects included in the study. The SAR values derived from the simulations fall well within the limits of legal guidelines. The baseline signal‐to‐noise ratio (SNR) advantage at 7.0 T was put to use to acquire 2D CINE images of the heart with a very high spatial resolution of (1 × 1 × 4) mm3. The proposed coil array supports 1D acceleration factors of up to R = 4 without significantly impairing image quality. Conclusion: The 16‐channel TX/RX coil has the capability to acquire high contrast and high spatial resolution images of the heart at 7.0 T. J. Magn. Reson. Imaging 2012;36:847–857. © 2012 Wiley Periodicals, Inc.